Collaborative Governance Dalam Perencanaan Pembangunan di Kabupaten Bekasi Provinsi Jawa Barat - Ika Sartika (Post Graduate School of Government Science, 2024)
Development planning is a crucial aspect in the implementation of the regional government, but the developments carried out so far tend to be planned centrally was dominated by the regional government. The collaborative governance approach to development planning is believed to be able to improve the quality of development planning that is oriented towards regional progress and community welfare. The study aims to examine collaborative governance in regional development planning along with supporting and inhibiting factors for collaborative governance in regional development planning in Bekasi Regency. The study uses a qualitative descriptive research design, where research data is obtained through data collection techniques of interviews, observations, and documentation studies. The analysis technique uses descriptive techniques including data collection, data condensation, data presentation, and drawing conclusions. The results of the study are as follows: 1) Collaborative governance in regional development planning is not optimal in terms of the weak implementation of face-to-face dialogue, low mutual trust built between collaboration actors, and lack of public trust in the regional development planning process, as well as lack of mutual understanding with the dynamics of differences in interests in the process of preparing regional development planning; 2) Collaborative governance in development planning is supported by the existence of basic rules in the form of regulations at the central and regional levels as references in regional development planning, the availability of adequate human resources in regional development planning, and the facilitative leadership of the Acting Regional Head who is quite proactive in regional development planning. Meanwhile, the inhibiting factors are the absence of a mechanism to increase community participation and the dynamics of differences in interests in regional development planning. Research suggestions require regional governments to initiate joint cross-sectoral forums and community elements that hold intensive dialogues, as well as increasing socialization and education of the community so that they can be proactively involved in providing input and criticism of regional development planning. Keywords: Collaborative Governance, Regional Government, Regional Development Planning.